Origin and Alteration of Organic Matter in Termite Mounds from Different Feeding Guilds of the Amazon Rainforests - Siebers, N.; Martius, C.; Eckhardt, K-U.; García, M.V.B.; Leinweber, P.; Amelung, Wulf (Public Library of Science, 2015)
The impact of termites on nutrient cycling and tropical soil formation depends on their feeding habits and related material transformation. The identification of food sources, however, is difficult, because they are variable and changed by termite activity and nest construction. Here, we related the sources and alteration of organic matter in nests from seven different termite genera and feeding habits in the Terra Firme rainforests to the properties of potential food sources soil, wood, and microepiphytes. Chemical analyses comprised isotopic composition of C and N, cellulosic (CPS), non-cellulosic (NCPS), and N-containing saccharides, and molecular composition screening using pyrolysis-field ionization mass spectrometry (Py-FIMS). The isotopic analysis revealed higher soil δ13C (-27.4‰) and δ15N (6.6‰) values in nests of wood feeding Nasutitermes and Cornitermes than in wood samples (δ13C = -29.1‰, δ15N = 3.4‰), reflecting stable-isotope enrichment with organic matter alterations during or after nest construction. This result was confirmed by elevated NCPS:CPS ratios, indicating a preferential cellulose decomposition in the nests. High portions of muramic acid (MurAc) pointed to the participation of bacteria in the transformation processes. Non-metric multidimensional scaling (NMDS) revealed increasing geophagy in the sequence Termes < Embiratermes < Anoplotermes and increasing xylophagy for Cornitermes < Nasutitermes, and that the nest material of Constrictotermes was similar to the microepiphytes sample, confirming the report that Constrictotermes belongs to the microepiphyte-feeders. We therewith document that nest chemistry of rainforest termites shows variations and evidence of modification by microbial processes, but nevertheless it primarily reflects the trophic niches of the constructors.